Influence of Ni to Co ratio supported on ZrO2 catalysts in phenol steam reforming for hydrogen production - Nabgan, W. (Elsevier Ltd, 2016)
In this work, catalytic steam reforming of phenol for hydrogen production was investigated. This study focuses on the effects of Ni to Co ratio supported on ZrO2 catalysts. The NixCoy/ZrO2 (x = 0, 1, 2, 3, 4 where x + y = 4) catalysts were prepared by impregnation method. Steam reforming activity was tested in a fixed bed reactor at 600 °C using a feed of phenol/water mixture at a molar ratio of 1:9 and a constant liquid feed rate of 0.36 ml/min. The catalysts were characterized by BET surface area, X-ray diffraction (XRD), transmission electron microscopy (TEM), NH3 Temperature-Programmed Desorption (NH3-TPD), CO2 Temperature-Programmed Desorption (CO2-TPD), H2 Temperature-Programmed Reduction (H2-TPR) and thermo-gravimetric analysis (TGA). The increase in the Co content from 0 to 4, caused a decrease in the crystal size, the t-ZrO2 phase and the reducibility of the catalysts. However, it only slightly affected the total surface area. It was found that metallic Ni4 and Co4 catalysts have lower activity towards phenol steam reforming and deposit higher coke due to having higher acidity sites compare to bimetallic catalysts. In contrast, Ni3Co1 displayed a superior catalytic activity among all the catalysts, suggesting the presence of the highest basic site and high coking resistance. Phenol conversion of 53.5% and hydrogen yield of 50.4% were achieved with the Ni3Co1 catalyst, even though its activity decreased by increasing the cobalt content.